Contribuição sociocultural do colégio estadual Benedito Rokag, terra indigena Kaingang Apucaraninha (Tamarana, PR) - Aguilar López, Flor Magali (2016)
The education of indigenous people is conceived in the dynamics of socialization, based on principles, organization, Cosmo vision and cosmology of the different tribes, that is, the education is not restricted to institutions, because it is an element inherent to the culture. The indigenous scholastic education in Brazil has gone through significant advances after the structuring of indigenous movements of the 1980s, supported by the legal landmark in the Federal Constitution of Brazil of 1988, which recognizes the different Brazilian cultures and languages. One such fundamental right of the indigenous people is the access to a differentiated education. This way, this research analyzes how the indigenous population of Kaingang Apucaraninha (Tamarana, PR) interprets the creation of the “Colégio Estadual Benedito Rokag” (Benedito Rokag State School) inside the village, and compares the time when the natives had to commute to the nearest district headquarters to go to high school, as well as the identification of the differentiated teaching processes, the influence generated by the school in community interaction, and the construction of the social economic identity of the indigenous people. The instruments used in this research for data collection were the bibliographical revision, semi-structures interviews and direct observation. The results of the field research indicate the principal difficulties the natives had in order to go to high school in a rural district close to the Indigenous Reservation, prejudice being one of the main ones, as well as the benefits and challenges associated with the implementation of the School in the village – the main benefit being the reconstruction of social and cultural identity of the indigenous youth. This way, the differentiated teaching methods are a precious alternative to the appreciation of indigenous culture, at the same time that they present new issues that must be discussed in the academic area, specifically with the indigenous people.